PENINGKATAN MUTU PENDIDIKAN MADRASAH MELALUI PEMBANGUNAN BUDAYA ORGANISASI - Hadi Laksono; H. Majeri; Rita Sukaesih; Budi Hermawan; Taufik (Fakultas Agama Islam Universitas Wiralodra, 2022)
IMPROVING THE QUALITY OF MADRASAH EDUCATION THROUGH DEVELOPMENT OF ORGANIZATIONAL CULTURE This study aims to describe and analyze what, why and how to improve the quality of madrasa education through organizational development. This research uses library research method and includes qualitative research. From this research, it was found that improving the quality of madrasa education has a large enough contribution in the world of education. Improving the quality of education refers to the process carried out in improving the quality of education. The role of organizational culture in an organization includes being able to improve performance, commitment from members of the organization, creating a family atmosphere, cohesiveness, learning resilience, enthusiasm to move forward, encouragement to work hard and never give up so that a conducive organizational culture can be realized so that it can be easy to improve. quality of madrasa education. Factors that support organizational values ​​such as quality culture, discipline culture, and hard work culture that are applied in the madrasa environment. Meanwhile, what can be an obstacle to the development of organizational culture is a lack of understanding of the vision and mission and goals of the madrasa, poor internal relations between educators and facilities and infrastructure that are less than optimal.